The correlation between infections by human papillomavirus types 6/11 and 16/18 and mammary gland hyperplasia with glandular thickening - Xiaoqun, Deng; Xiaoli, Long; Jun, Li; Yang, Xiaojuan (Cellular and Molecular Biology, 2019)
The aim of the present study was to investigate the correlation between human papillomavirus (HPV) type 6/11 and 16/18 infections and glandular thickening mammary gland hyperplasia in order to explore methods for preventing glandular thickening mammary gland hyperplasia. A total of 240 patients with glandular thickening mammary gland hyperplasia who were treated by surgery in our hospital from January 2012 to June 2017 were enrolled in the present study. The hyperplastic breast tissue and adjacent normal breast tissue were taken to test HPV type 6/11 and 16/18 infections using conventional PCR and in situ hybridization techniques. The correlations between HPV type 6/11 and 16/18 infections and glandular thickening mammary gland hyperplasia were analyzed using statistical methods of chi-square test. The infection rates of HPV type 6/11 and 16/18 in the hyperplastic breast tissue were 31.95% and 34.91%, respectively and 11.83% and 14.79% in the normal breast tissue, respectively. The differences were statistically significant (all p<0.05). HPV type 6/11 and 16/18 infections may be closely related to the development of glandular thickening mammary gland hyperplasia, and may be one of the causes of glandular thickening mammary gland hyperplasia.